Dampak Mal Tunjungan Plaza Terhadap Sektor Ekonomi Masyarakat Sekitar - Alifia, Rania; Kristiyanto , Sony (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of the study was to determine the impact of Tunjungan Plaza Mall on the economic sector of the community in Kedungdoro Village, Tegalsari Subdistrict, Surabaya. The research informants were 9 people. Data collection techniques consist of observation, interview, and documentation. The results of this study indicate that: the impact of the existence of Tunjungan Plaza Mall includes positive impacts and negative impacts, namely positive impacts including increased income in the form of an increase in the number of MSMEs, an increase in the number of boarding rentals, employment and the application of CSR to the community around Tunjungan Plaza. While the negative impacts of the existence of Tunjungan Plaza Mall include noise due to activities around the mall, and congestion due to stalls and illegal parking that stands around the mall area. The attitude of the community towards the existence of Tunjungan Plaza Mall is that the community is quite benefited in the economic sector, although on the other hand there are some negative impacts that arise.